1991
DOI: 10.1038/354245a0
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interaction of an initiator-binding transcription initiation factor and the helix–loop–helix activator USF

Abstract: Transcription initiation by mammalian RNA polymerase II is effected by multiple common factors interacting through minimal promoter elements and regulated by gene-specific factors interacting with distal control elements. Minimal promoter elements that can function independently or together, depending on the specific promoter, include the upstream TATA box and a pyrimidine-rich initiator (Inr) overlapping the transcription start site. The binding of TFIID to the TATA element promotes the assembly of other fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
355
4
5

Year Published

1996
1996
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(380 citation statements)
references
References 24 publications
16
355
4
5
Order By: Relevance
“…see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure. The role and form of the TATA box are also more complicated than originally conceived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure. The role and form of the TATA box are also more complicated than originally conceived.…”
Section: Discussionmentioning
confidence: 99%
“…TAFII28 and RXR ; [2]). In a number of cases there also appears to be specific binding by factors other than TBP to an ' initiator ' motif downstream from the TBP-binding site [3][4][5][6][7][8][9][10][11][12]. There is increasing evidence that particular DNA sequences in the core promoter, other than the TBP-and initiator-binding motifs, play a pivotal role in controlling whether a particular TBP\TAFII complex [13] or other non-TFIID factor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the HS2 sequence has been shown to contain DNA motifs that bind to many transcription factors such as NF-E2 and Ap-1 (33,35,46,48,49), GATA (22,39,49), YY1 (5,12), and USF (4,5,12,40,49). NF-E2, AP-1, and GATA have been suggested to be capable of recruiting and assembling the transcriptional machinery (16,53), and USF and YY1 have been reported to be capable of stimulating transcriptional initiation from their respective binding sites (25,26,41,44). The presence in the enhancer complex of transcription factors intimately associated with the transcriptional machinery suggests that the HS2 enhancer complex may also constitute a transcriptional complex (6) and thus may be capable of initiating enhancer transcription from defined sites in the HS2 enhancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Inr element is usually defined as a weak consensus YYCAYYYYY, where Y is a pyrimidine base (32). The initiator binding protein TFII-I stimulates basal transcription from the Inr element (33). Myc can bind TFII-I and form a complex associated with the Inr sequence that prevents transcriptional activation from Inr (34).…”
Section: Myc Represses the P21 Promoter By Its Proximal Region In Humanmentioning
confidence: 99%